KASIDAH BURDAH AS A RITUAL MEDIA FOR REJECTING BALA - Maslina, Maslina (UIN ANTASARI BANJARMASIN, 2023)
This research is about kasidah Burdah as a ritual media for rejecting bala to know the background of reading kasidah Burdah as a ritual medium for rejecting bala and describes the procession it and Burdah's belief in the ritual of rejecting bala in the community of Teluk Labak Village, North Daha District. The research method is qualitative with the type of research using field research which is descriptive and uses a Sociology of Religion approach. Data collection techniques used are observation, interviews, and documentation. While the data analysis techniques used are data collection, data reduction, data presentation, and verification or concluding. The results of this research is showing that the background reading of Burdah as a ritual media for rejecting bala and Burdah's belief in the ritual of rejecting bala carried out in Teluk Labak Village is as tawassul and repentance to the Prophet Muhammad SAW to prevent harm, calamity and others both for individuals or community groups. The implementation procession at night starts from the Hajat prayer in the congregation, reading Surah Yâsîn, Isha prayer and going down to the field to go around chanting Burdah, parading the book of al-Bukhârî, holy Qur’an, and reading selected prayers accompanied by beating drums from the beginning of the house to the end of the house. People's trust to carry out Burdah in the ritual of rejecting bala is expected to get safety, tranquility, and blessing.